The Influence of Independent Directors, Insider Ownership and Scientific Connections on Risky R&D Investments: Evidence from Emerging Markets - Stepanova, Anastasia; Tereshchenko, Anna (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Anastasia N. Stepanova - National Research University The Higher School of Economics, E-mail: anstepanova@hse.ru Anna Alexandrovna Tereshchenko - National Research Institute "Higher School of Economics R&D projects in the pharmaceutical industry are extremely risky and bring benefits in the long-run period. Self-interested managers try to avoid risk and underinvest in R&D. In this paper we study the effect of independent directors, insider ownership and scientific connections on R&D investments. Independent directors and insider ownership can mitigate the agency problem by additional monitoring and convergence of interests. Scientific collaboration promote technological development and increase R&D. The research reveals the difference of the effects in emerging and developed markets.In emerging markets theproportion of independent directors is positively connected with R&D investments. Such results can be explained by the fact that independent directors monitor risk-averse managers that underinvest in risky but perspective projects. Scientific connections significantly positively influence R&D investments. Empirical evidence also shows that companies with a higher proportion of independent directors have more collaborations with scientific institutions in emerging markets. Insider ownership also has no significant influence on R&D investments. Such a result can be explained by the fact that not all the insiders can influence the investment process. Moreover, beneficial owners can lack industry specific knowledge that allows them to monitor the process. In developed markets the situation is different. The proportion of independent directors is associated with lower R&D investment intensity. As R&D investments are extremely high in developed markets, we suppose that the overinvestment problem can exist. Thus, better corporate governance can decrease the investments closer to an optimal level. Scientific connections and insider ownership are not a significant factor. The research has wide policy implications. The results can be used by shareholders and government regulating institutions in creating optimal management structures.